Field seed germination and conservation of plants of beans depending on the seed sowing rates - Рожков, А. О.; Труш, О. К. (Scientific Progress & Innovations, 2018)
The results of three year research concerning the influence of seed sowing rates on field seed germination, conservation and quantity of plants before harvesting common beans varities which are different according to the morphobiotype were elucidated. The influence power of seed sowing rates on the changeableness of these indices during the years of different weather conditions in vegetation period was determined. It was ascertained that field seed germination of haricot beans varieties under studying according to different seed sowing rates was on the same level. Weather conditions influenced the changeableness of the indices in field germination of haricot beans seeds most of all at the beginning of seed germination. The plants’ conservation depended on sowing rate mainly till the vegetation end. The gradual increase of seed sowing rate caused the considerable decrease of plant conservation indices. In particular, the increase of sowing rate from 300 to 400 thousand pcs/ha caused the decrease of plants conservation by average 1.2 %, and the increase of seed sowing rate from 600 to 700 thousand pcs/ha – by 6.5 %. This appropriateness was marked in all the varieties during all the years of the research. Panna variety was the best one among the varieties under studying concerning the plants conservation indices. Under more favourable weather conditions of growing the field germination of this variety was not higher than that of Pervomaiska and Dokuchaievska ones. But under conditions of moisture short supply, high temperature during germination this variety had an advantage. So, before harvesting the conservation of Panna varieties plants on all the variants of seed sowing rate was not lower than 67.0 %, while this index was lower than 60.0 % for Pervomaiska and Dokuchaievska varieties. Owing to higher indices of plants conservation for Panna variety during years of unfavorable weather conditions for seed germination, the plants quantity of this variety was higher than that of other ones when harvested. The maximum quantity indices of plants, before harvesting was noticed in 2015. In particular, before harvesting the plants quantity of Pervomais’ka, Dokuchaievs’ka and Panna varieties amounted average to 22.0, 23.0, 28.5 pcs/m2 correspondingly to seed sowing rates, according to the HIP05 the effect of this factor – 1.1 pcs/m2. The increase of seed sowing rate caused the gradual increase of plants quantity before harvesting. But the considerable increase of plants quantity before harvesting when seed sowing rate rose from 600 to 700 thousand pcs/ha took place only in 2017 when this increase was within HIP05 in 2015 and 2016. So, the increase of seed sowing rate in haricot beans varieties under studying from 600 to 700 pcs/ha can ensure the increase of plants quantity before harvesting only during the years of favourable weather conditions. According to the plants conservation indices, the plants quantity before harvesting under the influence of weather conditions was more stable concerning Panna variety. In particular, according to the seed sowing rates the maximum divergence scope of plants quantity in Dokuchaievs’ka, Pervomais’ka and Panna varieties amounted average 19.2, 14.1, and 11.4 % correspondingly during the years of research. Under the weather conditions in 2015 and 2016 before harvesting the maximum plants quantity was on the variants of seed sowing rate amounting 600 thousand pcs/ha. The increase of sowing rate to 700 thousand pcs/ha did not ensure a considerable increase of haricot beans plants quantity before harvesting during these years. In 2017 the maximum quantity of haricot beans plants of all the varieties was on the variants of maximum seed sowing rate – 700 thousand pcs/ha. At the same time this increase did not exceed 5 % in comparison with the sowing rate amounting 600 thousand pcs/ha.